Analisa Model Matematik Arus Sejajar Pantai Pada Groin Seri Permeable - Adi Surya Pria Pranata; Novi Andhi Setyo Purwono; Ary Sismiani (Techno (Jurnal Fakultas Teknik, Universitas Muhammadiyah Purwokerto), 2018)
This research is the mathematical model has been made with two groins, permeable and impermeable groins, with the variation is in length and distance; 50 meters, 100 meters, 150 meters and 200 meters. A modelling has been done by using the data of physical modeling study by Chen., et al, 2003, and used as input to the simulation of mathematical models using 2D Boussinesq software.Results of the research showed the influence of variation model long distance between the groins, the reduction of longshore current velocity along the coast with an average 59.21% reduction for the double permeable groin with 50 meters long, 76.02% for 100 meters, 79.50% for 150 meters, 80.49% for 200 meters. The reduction of longshore current velocity along the coast are 57.42% for an impermeable groin groin double with 50 meters, 84.61% for 100 meters, 150% for 88.89 meters, and 89.91% for 200 meters. The distance variation between one groin to the other groin has a result that a longer permeable or impermeable groin affects the reduction longshore current velocity along the coast of the Surf Zone with the addition of longshore current velocity reduction occurs along the coast up to 20%. Reduction of longshore current velocity along the coast by the permeable and impermeable groin Permeable and impermeable groins has not been significantly occured in the long-term groin area exceeding Surf zone with an average additional reduction up to 5%. The longshore current velocity approaching the speed of currents along the coast for the existing conditions at a distance up to 2.4 times of length of groins. And the distance between the groins are too close if we compare to the long groins causing the current direction of movement towards the sea (rip Current).